Antibiotic use knowledge and behavior at a Ugandan university - Nambatya, Jacqueline Lule; Nyairo, Sarah; Bironse, Micheal; Kacwiya, Samantha; Musigunzi, Norman; Kamulegeya, Adriane (International Journal of Infection Control, 2011)
The study evaluated knowledge, attitude and behaviour of antibiotic usage in two student groups at Makerere University in Uganda. Out of 30,000 students enrolled at the university, 1000 were asked to participate by filling a self administered questionnaire. The sampling group was divided into Group A which included students from the College of health sciences and Group B made of students of other faculties. The response rate was 72.1% and 58.8% were male. The sample size distribution didn’t differ from the university gender distribution Z=1.57, p< 0.05. The use of antibiotics to avoid illness was reported by 24.0% in Group A and 31.8% in Group B (P< 0.05). When asked the course of action if they felt the antibiotic being used was not helpful, 35.1% in group A and 50.6% in B said they would go back to the same health care worker for advice while 1.4% and 9.9% respectively would switch health care provider. Up to 69.3% of the respondents reported antibiotics use in the last twelve month. The most common symptoms reported as the primary reason for antibiotic use was cough at 16%, followed by sore throat at 7.1% and common cold at 6.1%. The high reliance on health care personnel for prescription was rather encouraging and it gives health workers a window of opportunity to promote rational antibiotic use when prescribing to patients. However, for this to materialize the health workers must be aware of antibiotic resistance and ways to combat it. Therefore constant training and encouragement must be given to the health care workers and the public.